Arabic Language Program Management in Islamic Boarding School of Daarul Ukhuwwah Malang - Dian Ahmad Jufrih; Suci Ramadhanti Febriani; Nur Kholid; Abd Fattah (IAIN Salatiga, 2022)
The purpose of this research is to describe matters related to the management of the Arabic language program at Daarul Ukhuwwah Putri 2 Islamic Boarding School in Malang in the form of its planning, organizing, implementing and evaluating. This study used descriptive qualitative methods. The data is collected through observation and interview. It is then carried out by analyzing data condensation, data display and drawing and verifying conclusions. The results showed that the planning of this program at Daarul Ukhuwwah adopted the Kuliyatul Muallimin Al Islamiyah Curriculum at Pondok Modern Darussalam Gontor, Ponorogo. Besides, its organizational structure is formed for each division. One of them is the Central Language section which is held directly by the teacher (Ustadzah). The implementation of the program include: Arabic language learning in class, learning mufradât, muhadatsah, muhadhoroh and language festivals. Finally, the evaluation of the program is conducted each week, month and year.